Kualitas Pelayanan Terhadap Keputusan Berkunjung ke Hotel 88 Jakarta - Heny Ratnanningtyas; Andhalia Liza Marie; Gratia Wirata Laksmi; Pusparani Pusparani; Anis Darsiah; Mimi Enggriani (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study aims to determine the physical evidence, reliability, responsiveness, assurance and empathy for the decision to stay at Hotel 88 Jakarta. This type of research is descriptive quantitative with multiple analytical methods. The objects in this study are hotel guests staying at Hotel 88 Jakarta. The sampling technique uses accidental sampling. The sample of this research is 100 people hotel guests staying at Hotel 88 Jakarta. The results of the study partially show that physical evidence, reliability, responsiveness, assurance and empathy have a significant effect on the decision to visit. Hotel 88 service quality is demanded to be able to provide products whose benefits are directly felt by consumers. Hotel 88 is expected to continue to improve service quality and service deficiencies can be evaluated by Hotel 88 so that it can be corrected so that consumer needs and desires are met.